Critical Analysis of Children's Legal Skills in the Hanafi Mazhab - Andi Wijaya; Siti Nurhaliza (Indonesian Journal of Islamic Law, 2021)
This research explores the concept of legal proficiency or " Ahliyyah " in the Hanafi Mazhab of thought , with a particular focus on the " mumayyiz " phase which marks when children begin to differentiate between good and bad at the age of seven. This research uses a qualitative approach, collecting data from classical texts, legal documentation, and interviews with ulama and legal practitioners, to explore how children's legal skills are defined and applied. The results of the study show that there are significant variations in the application of Ahliyyah principles in various social and cultural contexts, reflecting the flexibility and adaptation of the Hanafi Mazhab of thought to diverse societal conditions. This study highlights the importance of standardization in the application of law and the need for more inclusive legal education for legal practitioners, to increase consistency and fairness in legal practice. The social and ethical implications of legal protection for children in this school of thought show the importance of a holistic approach that combines moral considerations and children's welfare in all legal decisions. The conclusions of this research emphasize the need for policies that are more dynamic and responsive to the needs of children, supporting their welfare while maintaining the integrity and adaptability of Islamic law within the Hanafi Mazhab of thought.